Efficiency of Modern Power Plants of Thermal Power Stations - B. V. Yakovlev; A. S. Grinchuk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2007)
The paper considers efficiency and prospects in development of different types of fossil-fuel power plants – gas turbine, steam turbine and combined (gas and steam) cycles.The paper provides information on plant selection, fuel consumption, specific output cost. It describes main advantages of various power plants.